Unanswered Questions and Hypotheses about Domestic Cat Behavior, Ecology, and the Cat–Human Relationship - Dennis C. Turner (Animals, 2021)
After recent publication of several reviews covering research results from the last 35 years of domestic cat studies, a number of important unanswered questions and hypotheses have arisen that could interest active researchers, especially those beginning their academic careers. Some sections of this paper concern methodologies that have yielded new insights and could provide more in the future; other sections concern findings and interpretations of those that need further testing. First, hypotheses arise from combining subjective (or psychological) assessments of cat and human personality traits and observational (ethological) studies of cat–human interactions: e.g., do owners with high attachment to their cats interact differently with them than owners with low attachment levels? New analytical methods of dyadic interaction observations open the door for testing further hypotheses. In particular, the Theme® (Noldus bv, NL) program could be used to determine if there are differences between cat breeds in interaction patterns with people, which is not only of interest to owners but also therapists employing cats in their practices. Cat breed differences have been found using subjective ratings, but these need to be corroborated by direct observational data from the home setting and/or non-invasive colony observations, since ratings based on anthropomorphic projections might not be reliable. This should be done before searching for the genetic basis of such differences. Reliable information on breed differences is also needed before prescribing certain breeds for animal-assisted interventions. A model has predicted that the degree of socialization as a kitten affects cats’ responses to positive and negative experiences with unfamiliar humans and their formation of feline–human relationships later on. This needs to be tested in an ethically approved manner on cats of known socialization status and has enormous consequences for cat adoptions from animal shelters. Observations of human–cat interactions have yielded many correlations, which can be tested by non-invasive manipulations of human behavior in the home setting. Examples of these will be given and are of general interest to the cat-owning public. A review of first findings on social cognition in cats has resulted in further unanswered questions and hypotheses. Finally, two aspects of domestic cat ecology will be considered (effects on wildlife and space utilization), which are of great interest to the public and conservationists alike.